Formes et contextes de production des hétéro-reprises immédiates de la structure des énoncés avec subordination, chez deux enfants, entre 5 ans ½ et 6 ans ½ - Heurdier, Julien (My University, 2008)
The aim of the present paper is to study the link between immediate structural hetero-repetitions and production of complex utterances (such as completives, infinitives, and relatives) quantitatively. We focus on this process made by two French children between five and six and by an adult, in narration activities. We look at the forms of complex utterances which are reemployed by the children or by the adult, and at the context in which these immediate repetitions are produced. Leaning on longitudinal observations, we also try to highlight the stake of the third turn in the exchange. Our short study tends to confirm previous findings about repetitions by young children (Clark & Bernicot, 2008): our two subjects can use the structure of complex utterances introduced by the adult when they add new and further information to the exchange. For the adult, structural repetition is mainly used to confirm the child's production or to add new and other information. After the repetition of a complex utterance, the two children tend to re-repeat the adult's utterances in a third turn whereas the adult underuses this strategy.